Klasyczna i nowoczesna koncepcja kultury politycznej a problem uczuć - Filipkowski, Janusz (Zeszyty Naukowe Katolickiego Uniwersytetu Lubelskiego Jana Pawła II, 2021)
Affect makes a crucial component of political culture. This article addresses how affective factors influence the level of political culture. Two main concepts of political culture can be distinguished: the classical concept, which is anchored in the concept of classical philosophy; and the modern concept, rooted in the rationalist principles of enlightenment. Under the classical concept, political culture requires that the sphere of feelings and emotions be subordinated to reason, and to the principles resulting from the objective truth as recognized by reason. The modern concept rejects the idea of objective truth, and hence reason is reduced to the role of a tool for satisfying subjective and changing human emotional drives, which can be destructive both for personal development of individuals and for the functioning of state communities.